INVENTARISASI RAGAM HIAS ACEH PADA ILUMINASI MUSHAF AL-QURAN KUNO KOLEKSI PEDIR MUSEUM DI BANDA ACEH - Niko Andeska; Indra Setiawan; Rika Wirandi (Gorga : Jurnal Seni Rupa, 2019)
AbstrakIluminasi atau seni naskah (the art of the book), dapat diartikan sebagai garapan visual yang bersifat dekoratif yang terdapat pada naskah yang berfungsi sebagai penghias. Pada dasarnya digunakan untuk memperindah bagian tertentu, terutama pada halaman depan naskah (frontispiece). Dalam naskah kuno karya ulama Aceh diketemukan berbagai bentuk iluminasi yang mengadopsi gaya ragam hias lokal Aceh. Keindahan iluminasi dalam khazanah naskah kuno karya ulama Aceh, terutama yang terdapat mushaf Al-Quran yang terhimpun menjadi koleksi lembaga-lembaga non pemerintah (swasta) di Kota Banda Aceh saat ini belum sepenuhnya tersentuh oleh kajian-kajian yang mengarah pada aspek rupa. Baik dari segi pendataan yang komprehensif hingga analisis mendalam dalam perspektif seni rupa.Penelitian yang berjudul “Inventarisasi Ragam Hias Aceh Pada Iluminasi Mushaf Al-Quran Kuno Koleksi Pedir Museum di Banda Aceh” bertujuan untuk mengkaji aspek rupa yang memfokuska n pada ragam hias Aceh pada iluminasi pada beberapa mushaf Al-Quran koleksi Pedir Museum. Penelitian ini menggunakan metode penelitian kuantitatif, dengan menggunakan teknik pengumpulan data melalui observasi, wawancara, dokumentasi, dan pendataan. Data-data yang telah terkumpul kemudian dilakukan proses pengindentifikasian, pengkatagorisasian, dan analisis data dengan mengunakan metode digitalisasi ragam hias pada beberapa mushaf Al-Quran koleksi Pedir Museum Banda Aceh. Penelitian ini diharapkan dapat mendata, mendokumentasikan, meninventarisir, serta analisis karakteristik ragam hias Aceh yang terdapat pada iluminasi mushaf Al-Quran koleksi Pedir Museum.Kata Kunci: ragam hias Aceh, mushaf Al-Quran.AbstractIllumination or manuscript (the art of the book), can be interpreted as a decorative visual work that is contained in the manuscript that serves as a decoration. Basically used to beautify certain parts, especially on the front page of the script (frontispiece). In ancient manuscripts by Acehnese scholars, various forms of illumination were adopted which adopted the local Acehnese decorative style. The beauty of illumination in the treasures of ancient manuscripts by Acehnese ulama, especially those contained in the Al-Quran Manuscripts compiled into a collection of non-governmental institutions (private) in the city of Banda Aceh at this time has not been fully touched by studies that lead to visual aspects. Both in terms of comprehensive data collection to in-depth analysis in the perspective of fine arts. The study entitled "Inventory of Aceh Ornamental Variations in Illumination of Ancient Al-Quran Manuscripts in the Pedir Museum Collection in Banda Aceh" aims to examine visual aspects that focus on the Acehnese ornamental variety in illuminations on several Al-Quran Manuscripts from the Pedir Museum collection. This research uses quantitative research methods, using data collection techniques through observation, interviews, documentation, and data collection. The data that has been collected is then carried out the process of identifying, categorizing, and analyzing the data by using the digitizing method of ornamental variance in several Al-Quran Manuscripts from the Banda Aceh Pedir Museum collection. This research is expected to be able to record, document, inventory, and analyze the characteristics of Aceh's ornamental variations found in the illumination of the Al-Quran Manuscripts from the Pedir Museum collection.  Keywords: variety of ornamental Aceh, Al-Quran manuscripts.